Kolaborasi Perguruan Tinggi dan Dunia Industri dalam Meningkatkan Kesiapan Kerja Siswa SMK Kota Tegal - Erni Unggul Sedya Utami; Ghea Dwi Rahmadiane; Bahri Kamal; Agung Hendarto (Jurnal Pengabdian Masyarakat - PIMAS, 2026)
A community service activity with the theme challenges and solutions to the world of work for vocational high school students in Tegal City" was carried out as an effort to improve the work readiness of vocational high school students in facing the challenges of the industrial world and increasingly competitive job competition. Problems faced by students include limited understanding of the needs of the world of work, the recruitment process, professional ethics, and the importance of developing soft skills. This activity was carried out at SMK PGRI Tegal City by a team of lecturers from Harkat Negeri University in collaboration with the Tegal City Manpower and Industry Office and the Tegal City HRD Forum involving 40 male and female students as participants. The implementation method used an educational-participatory approach through seminars, counseling, interactive discussions, job interview simulations, and sharing experiences from Human Resource Development practitioners. The results of the activity showed that participants experienced an 85% increase in understanding of the challenges and needs of the world of work, an 87% increase in readiness to face the job recruitment process, and a 90% positive response to the implementation method of the activity. Participants showed increased motivation in developing self-competence and work readiness. It can be concluded that this community service activity has succeeded in increasing students' insight, work readiness, and understanding of the needs of the industrial world as well as strengthening the synergy between universities, schools, local governments, and the industrial world in supporting the development of competitive and work-ready young human resources.